Nasal compartmentalization in Kogiidae (Cetacea, Physeteroidea): insights from a new late Miocene dwarf sperm whale from the Pisco Formation - Benites-Palomino A. (2021)
Facial compartmentalization in the skull of extant pygmy whales (Kogiidae) is a unique feature among cetaceans that allows for the housing of a wide array of organs responsible for echolocation. Recent fossil findings indicate a remarkable disparity of the facial bone organization in Miocene kogiids, but the significance of such a rearrangement for the evolution of the clade has been barely explored. Here we describe Kogia danomurai sp. nov., a late Miocene (c. 5.8 Ma) taxon from the Pisco Formation (Peru), based on a partially preserved skull with a new facial bone pattern. Phylogenetic analysis recovers K. danomurai as the most basal representative of the extant genus Kogia, displaying a combination of derived (incipiently developed and excavated sagittal facial crest) and plesiomorphic features (high position of the temporal fossa, and antorbital notch not transformed into a narrow slit). Furthermore, when compared with the extant Kogia, the facial patterning found in K. danomurai indicates differential development among the facial organs, implying different capabilities of sound production relative to extant Kogia spp. Different facial bone patterns are particularly notable within the multi-species kogiid assemblage of the Pisco Formation, which suggests causal connections between different patterns and feeding ecologies (e.g. nekton piscivory and benthic foraging). At c. 5.8 Ma, K. danomurai was part of a cetacean community composed of clades typical of the late Miocene, and of other early representatives of extant taxa, a mixture probably representing an initial shift of the coastal faunas toward the ecosystem dynamics of the present-day south-eastern Pacific. © 2021 The Palaeontological Association